PENINGKATAN KINERJA SUMBER DAYA MANUSIA MELALUI MOTIVASI, DISIPLIN, LINGKUNGAN KERJA, DAN KOMITMEN - Agung Prihantoro (Value Added : Majalah Ekonomi dan Bisnis, 2012)
This study aims to analyze the performance of teachers MTs and MA Salafiyah, Kajen, Margoyoso, Pati. This study uses the variables of motivation, discipline, and work environment to analyze the influence ot the teachers performance. In addition, this study also used a commitment as intervening variables to analyze the influence of teachers level of commitment to school. The population in this study were all teachers MTs and MA Salafiyah, Kajen, Margoyoso, Pati. This population totaled 110 teachers of 52 teachers MTs Salafiyah and 57 teachers MA Salafiyah. This study used cencus method is to give the questionnaire to the entire population of 110 teachers. Data was collected using a questionnaire method is by providing a list of questions or questionnaire directly to the respondensts. Techniques of data analyze in this study using SEM analysis (Structural Equation Model) which is operated through a pogram SMARTPLS. The results showed that the variables of motivation, discipline, and work environments have a significant positive effect on commitment. Variables motivation, discipline, commitment, and the work environment showed significant positive results on the performance of human resources. Key words :  Human Resources Performance, Commitment, Work Environment, Discipline, Motivation